Performance and exhaust emissions of a compression ignition engine operating on ester fuels at increased injection pressure and advanced timing - Yahya, Azmi; Marley, Stephen J. (Elsevier BV, 1994)
Effects of increased injection pressure and advanced injection timing on the performance and exhaust emission characteristics of a direct injection, naturally aspirated John Deere 4239D engine operating on methyl soyoil ester (IV (iodine value) = 125-135) and methyl tallow ester (IV = 47-53) were studied. The test engine was fully instrumented to provide all the required measurements for determination of the needed performance and exhaust emission variables. Four treatment combinations consisting of two levels of injection pressure (18.6 MPa and 24.1 MPa) and two levels of injection timing (19° before top-dead-centre (BTDC) and 14° BTDC) were employed. The physical and chemical properties of the test fuels were earlier determined in accordance to the ASTM and AOCS standards. Results indicated that the engine operating on ester fuels at the manufacturer's injection pressure-timing setting (18.6 MPa and 14° BTDC) had lower carbon monoxide and unburned hydrocarbon carbon emissions and smoke levels, despite a slight increase in brake specific fuel consumption, as compared with when it was operating on No. 2 diesel fuel (control fuel). There were no significant differences in the engine brake specific fuel consumption and brake thermal efficiency between the ester fuels. However, between the two ester fuels, the saturated ester fuel (methyl tallow ester) showed slightly lower carbon monoxide and unburned hydrocarbons emissions, and higher smoke levels. The engine performance and exhaust emission characteristics of the engine operating on the ester fuels at advanced injection timing were better than when operating at increased injection pressure. Poor fuel combustion near the maximum operating power level was indicated with the engine operating on ester fuels at increased injection pressure. Complete fuel combustion was suppressed during high fuel flow probably due to the lack of oxygen within the spray envelope. Thus, fuels in some locations within the spray envelope that were too rich to burn escaped as unburned hydrocarbons, or burned incompletely causing high carbon monoxide and smoke levels in the exhaust emissions. Operating the engine at such conditions for extended periods could give rise to deposits problems in the combustion chamber. The engine performance and exhaust emission characteristics between the two ester fuels were almost similar at advanced injection timing and increased injection pressure.